2021
DOI: 10.1111/joor.13249
|View full text |Cite
|
Sign up to set email alerts
|

A world panorama of bruxism in children and adolescents with emphasis on associated sleep features: A bibliometric analysis

Abstract: Background and Objectives To present a world panorama of the published papers on bruxism in children and adolescents, emphasising the characteristics of studies related to the sleep features of these patients. Methods Literature searches were conducted in six databases without language or date restrictions. Data on the titles, types of study, main subjects, countries of origin, keywords, years of publication, authors and their network collaborations, journals and sleep studies were extracted and analysed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 55 publications
5
23
0
2
Order By: Relevance
“…Previous studies have pointed to a tendency of increasing number of publications over time, specially over the past (Jayaratne and Zwahlen, 2015;Celeste et al, 2016;Ribeiro-Lages et al, 2021). These findings corroborate with our data, although our results presented a less expressive absolute number, being 9 published articles, the highest number reached in a single year (2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous studies have pointed to a tendency of increasing number of publications over time, specially over the past (Jayaratne and Zwahlen, 2015;Celeste et al, 2016;Ribeiro-Lages et al, 2021). These findings corroborate with our data, although our results presented a less expressive absolute number, being 9 published articles, the highest number reached in a single year (2021).…”
Section: Discussionsupporting
confidence: 92%
“…A recent bibliometric analysis about bruxism in children and adolescents pointed Brazil with the highest number of publications in this area (131 publications, 18.06%). The authors highlight that this condition may be seen as a prevalent health problem in Brazil explaining the research focus (Ribeiro-Lages et al, 2021). It was also observed that Brazilian authors compose the top authors, presenting more publications in bruxism field than authors from other nationalities.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…O Bruxismo é definido como uma atividade repetitiva da musculatura mandibular, caracterizada pelo Apertamento e/ou Rangimento dos dentes que pode se manifestar, com base no ciclo circadiano, nos estados de vigília (Bruxismo acordado ou Bruxismo em vigília) ou durante o sono (Bruxismo do sono) 1 , com maior incidência em crianças do que em adultos e com tendência a diminuir com a idade 2 . Esta condição tem sido associada a fatores diversos, dos quais estão os patofisiológicos, como obstrução das vias aéreas, apneia do sono, refluxo gastroesofágico e distúrbios do sono 17,18 , os fatores genéticos 19,20 , os aspectos psicológicos, principalmente ansiedade, estresse e neuroticismo 4,21 , dentre outros, como respiração bucal, roer unhas e morder objetos 22,23 .…”
Section: Discussionunclassified